Towards Sustainable Food Security: Initiation of Adaptive Policies to the Climate Crisis in Baubau City, Southeast Sulawesi - Inzana, Nur; Asiri, La; Sari, Putri Mawang (Jurnal Pemerintahan dan Politik Lokal, 2024)
This research highlights the urgency of food security in Baubau City, Southeast Sulawesi, which is threatened by climate change and damage to agricultural land due to drought. This study aims to formulate adaptive policies to increase food security through analyzing the impacts of climate change and evaluating existing policies. This study maximizes qualitative methods through observation, documentation and interviews. The data that was successfully obtained was then transcribed and transferred into the NVivo 12 Plus analysis tool for data coding. Next, data visualization is carried out to assist analysis. This research found that climate change has significantly affected agricultural productivity and food availability in Baubau City through extreme rainfall fluctuations and increased temperatures. Declining crop yields and disrupted cropping patterns have led to local food shortages and increased food prices, especially for low-income families. To overcome these challenges, policies such as the Mother's Kitchen Garden Program and agricultural intensification need to be balanced with more comprehensive mitigation strategies, including the development of climate-resilient agricultural techniques, improved water management infrastructure, early warning systems, and farmer education. These findings emphasize the need for adaptive policies to improve food security and agricultural efficiency amidst the climate crisis.